Rapid development of homozygous lines through culture of isolated microspores in leafy crops of Brassicaceae Burnett - Elena A. Domblides; Olga A. Chichvarina; Anna I. Minejkina; Evgeniу L. Kurbakov; Viktor A. Kharchenko; Arthur S. Domblides; Alexey V. Soldatenko (Овощи России, 2019)
RelevanceBiotechnological methods are generally used to speed up breeding programs and to enhance genetic diversity, so the culture of isolated microspore in vitro can be regarded as one of very suitable methods. Nontraditional and uncommon vegetable crops belonging to Brassicaceae Burnett. are becoming more popular.MethodsAccessions of sarepta mustard (Brassica juncea L. Czern.) and rocket salad (Eruca sativa Mill.) were taken for the study with the aim to optimize the basic protocol for these species.ResultsAs a result of the study the optimum cultivation conditions have been determined for the species. Sizes of buds 2.5-3.5 mm long for sarepta mustard and 7.0-7.5 long for rocket salad which were used for cultivation had been experimentally defined. It was also shown that the cold pretreatment had improved the embryo yield. The nutritional NLN-13 medium with pH 6.1 and pretreatment at 32°C during a cultivation day had been shown to be more favourable for all accessions. All conditions that had been used were suitable for embryo formation. First divisions had been seen after 4 days of cultivation, while the embryos at primary cotyledonary stage only appeared after 2 weeks of cultivation. The embryo yield per 5 buds reached 25-30 and 5-7 in the sarepta mustard and the rocket salad, respectively. It is worth noticing that the root formation and plant adaptation had passed better and faster in sarepta mustard than in rocket salad. Thus, whole process of homozygous line developing can be completed for 4-5 months, making the breeding program 3 times shorter.